Hang on, monkey! - Neuman, Susan B. (Washington, D.C. : National Geographic, 2014)
This book uses simple vocabulary and fun pictures to capture the interest and help develop the skills of beginning readers. The crazy antics, humor, and fun information make this new reading experience a treat.
10
Keywords: Monkeys -- Juvenile literature; Monkeys -- Infancy -- Juvenile literature